2009
DOI: 10.1108/14691930910977798
|View full text |Cite
|
Sign up to set email alerts
|

Indian software and pharmaceutical sector IC and financial performance

Abstract: Purpose -This paper seeks to estimate and analyze the relationship between intellectual capital and corporate conventional financial performance measures of Indian software and pharmaceutical companies for a period of five years from 2002 to 2006. Design/methodology/approach -Annual reports, especially the profit and loss accounts and balance sheets of the selected companies for the relevant years have been used to obtain the data. International literatures on intellectual capital with specific reference to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
144
5
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 18 publications
(26 reference statements)
15
144
5
6
Order By: Relevance
“…For example, although some researchers [23,8,25] emphasized the role of intellectual capital in explaining the difference between book and market values of companies, the current study, like some similar studies [15,14,10], has not find any signs regarding the relationship between intellectual capital and market value of companies. On the other hand, as some researchers [34,30,26,17,12,10] confirm the role of intellectual capital in explaining the profitability, the current study also showed the mentioned relationship. This study includes significant themes for practitioners and managers of pharmaceutical companies and researchers who are interested in the topic of intellectual capital.…”
Section: Conclusion and Recommendationsmentioning
confidence: 58%
“…For example, although some researchers [23,8,25] emphasized the role of intellectual capital in explaining the difference between book and market values of companies, the current study, like some similar studies [15,14,10], has not find any signs regarding the relationship between intellectual capital and market value of companies. On the other hand, as some researchers [34,30,26,17,12,10] confirm the role of intellectual capital in explaining the profitability, the current study also showed the mentioned relationship. This study includes significant themes for practitioners and managers of pharmaceutical companies and researchers who are interested in the topic of intellectual capital.…”
Section: Conclusion and Recommendationsmentioning
confidence: 58%
“…Chen, 2009;Ghosh & Mondal, 2009;Shiu, 2006;Ting & Lean, 2009). This indicator-based method (called VAIC TM , Value Added Intellectual Coefficient) has been widely used, across sectors and countries, and provides a standardized measure, easy to understand and allowing benchmarking.…”
Section: Resultsmentioning
confidence: 99%
“…Artinya, bahwa HC (farmasis atau apoteker) dapat menjalankan CPOB yang merupakan SOP proses produksi obat sehingga kegiatan operasional perusahaan dapat berjalan dengan lancar dan mutu obat terjamin. Namun, hasil penelitian ini berbeda dengan salah satu hasil penelitian Ghosh dan Mondal (2009), yang menyatakan bahwa IC tidak berpengaruh pada produktivitas perusahaan farmasi dan software di India. Artinya, IC tidak berperan dan tidak berkontribusi pada produktivitas.…”
Section: Peran Penting Dan Kontribusi Ic Untuk Menunjang Kegiatan Opeunclassified
“…Dengan demikian, apabila dikaitkan dengan hasil penelitian sebelumnya bahwa penelitian ini mendukung dan mampu menjelaskan hasil penelitian lain, seperti hasil penelitian Sharabati et al (2010), Ghosh dan Mondal (2009), Bramhandkar et al (2007, Chen et al (2004), Cabrita dan Bontis (2007), Bontis et al (2000), Chen (2008), Stewart (1997), dan Mageza (2004 (lihat tabel 5). Artinya, bahwa farmasis yang berkualitas, unggul, mampu menjaga mutu obat, dan mampu melaksanakan CPOB dengan baik, dapat dipastikan akan menghasilkan mutu obat yang diminati oleh konsumen (lihat tabel 6).…”
Section: Peran Penting Dan Kontribusi Ic Untuk Menunjang Kegiatan Opeunclassified